Management by competence: a theoretical approach - Marin Granados, Laura (Revista Minerva, 2020)
The term competition in the business world had its beginnings in the 1970s and in human resource management, its greatest exponent being David C. McCleland, a professor at Harvard University; The results of his studies were published in 1973, the date that marked the beginning of management by competencies, with the title: "Selection by competence and not by intelligence." At present, the subject of management by competencies at the business level has been reopened, as it is a powerful tool that facilitates the increase of the competitiveness and sustainability of organizations and because of the importance of the development of human talent competencies to achieve the organizational goals and objectives. Therefore, it is necessary to understand what competencies are, the types of competencies to reach an understanding of the competency management model, elements that will be analyzed in this chapter.
Keywords: management; competition